Learn robotics with Raspberry Pi : build and code your own moving, sensing, thinking robots (No Starch Press, 2019)
"A beginner's guide to building and coding robots with the Raspberry Pi microcomputer. Each chapter teaches progressively complex lessons, from wireless control to line following, through detailed instructions and projects"--